STUDENTS’ PERCEPTION IN ENGLISH LEARNING USING ZOOM FOR THE EIGHTH GRADERS IN MTS MUHAMMADIYAH KARANGKAJEN YOGYAKARTA - Universitas Ahmad Dahlan, Thalia Savira Ristianti; Tri Rini Widiarti (Global Synthesis in Education Journal, 2023)
Zoom is a learning media for students and teachers in learning during Covid-19 pandemic. By using Zoom as alternative media in Covid-19, students try to adapt to the newest regulation in learning and the students must be have different opinion of Zoom. This study aims to determine: (1) students’ perception in English learning using Zoom (2) the advantages and the disadvantages of Zoom as learning media. The method in this research is mixed-method. The subjects in this research are eighth graders of MTS Muhammadiyah Karangkajen Yogyakarta consisting of 78 students. The sampling in this research is random sampling. Data are collected by questionnaire and interview which are analyzed using quantitative and qualitative methods. The results of this research shows that of a total 78 students, four students (5%) have a very positive perception, twenty-seven students (35%) have a positive perception, eighteen students (23%) have a neutral perception, twenty-two students (28%) have a negative perception, and seven students (9%) have a very negative perception. The advantages of Zoom are a share screen/presentation, board, screen record, raises hand, microphone, adjustable virtual background, and schedule meetings which simplifying the virtual learning. The disadvantages of Zoom are related to the signal, the application takes a lot of device memories and internet data.